Controllable Ceramic Green‐Body Configuration for Complex Ceramic Architectures with Fine Features. (30th January 2019) - Zhang, Danwei; Peng, Erwin; Borayek, Ramadan; Ding, Jun
Abstract: Fabrication of dense ceramic articles with intricate fine features and geometrically complex morphology by using a relatively simple and the cost‐effective process still remains a challenge. Ceramics, either in its green‐ or sintered‐form, are known for being hard yet brittle which limits further shape reconfiguration. In this work, a combinatorial process of ceramic robocasting and photopolymerization is demonstrated to produce either flexible and/or stretchable ceramic green‐body (Flex‐Body or Stretch‐Body) that can undergo a postprinting reconfiguration process. Secondary shaping may proceed through: i) self‐assembly‐assisted shaping and ii) mold‐assisted shaping process, which allows a well‐controlled ceramic structure morphology. With a proposed well‐controlled thermal heating process, the ceramic Sintered‐Body can achieve >99.0% theoretical density with good mechanical rigidity. Complex and dense ceramic articles with fine features down to 65 μm can be fabricated. When combined with a multi‐nozzle deposition process, i) self‐shaping ceramic structures can be realized through anisotropic shrinkage induced by suspensions' composition variation and ii) technical and functional multiceramic structures can be fabricated. The simplicity of the proposed technique and its inexpensive processing cost make it an attractive approach for fabricating geometrically complex ceramic articles with unique macrostructures, which complements the existing state of‐the‐art ceramic additive manufacturing techniques. Abstract : Additive manufacturing of dense ceramic articles with geometrically complex structures and intricate fine features : A combinatorial process of ceramic robocasting with photopolymerization using a low solid loading photocurable ceramic suspension is proposed to enable fabrication of reconfigurable flexible and stretchable ceramic green‐body. Sintering of such green‐body results in fine and dense ceramic articles with geometrically complex shapes.